TANGGUNG JAWAB PERDATA ATAS TINDAKAN LALAI KURATOR DALAM KEPENGURUSAN HARTA PAILIT (BOEDEL PAILIT) - Aditya Rizal Ranovianto; Merline Eva Lyanthi (Halu Oleo University, 2024)
This study aims to determine the Civil Liability for Negligent Actions of the Curator in the Management of Bankrupt Assets (Boedel Bankrupt). The method used in this study is the normative legal method, which is carried out by researching and reviewing theories, principles, legal concepts, and also relevant laws and regulations. The results of the study show that the Curator has broad duties and authorities in managing and settling bankrupt assets since being appointed by the Commercial Court Judge, and is responsible professionally and with integrity. If the curator is negligent to the point of causing losses, they can be held personally liable in accordance with Article 72 of the UUK and Articles 1365 and 1367 of the Civil Code.